Comparative Analysis of the Regulatory T Cells Dynamics in Peripheral Blood in Human and Porcine Polytrauma - Serve, Rafael; Sturm, Ramona; Schimunek, Lukas; Störmann, Philipp; Heftrig, David; Teuben, Michel P. J.; Oppermann, Elsie; Horst, Klemens; Pfeifer, Roman; Simon, Tim P.; Kalbas, Yannik; Pape, Hans-Christoph; et al. (Frontiers in Immunology, 2018)
Background: Severely injured patients experience substantial immunological stress in the aftermath of traumatic insult, which often results in systemic immune dysregulation. Regulatory T cells (Treg) play a key role in the suppression of the immune response and in the maintenance of immunological homeostasis. Little is known about their presence and dynamics in blood after trauma, and nothing is known about Treg in the porcine polytrauma model. Here, we assessed different subsets of Treg in trauma patients (TP) and compared those to either heathy volunteers (HV) and data from porcine polytrauma. Methods: Peripheral blood was withdrawn from 20 TP with injury severity scores (ISS) ≥16 at the admittance to the emergency department (ED), and subsequently on day one and at day three. Ten HV were included as controls (ctrl). The porcine polytrauma model consisted of a femur fracture, liver laceration, lung contusion, and hemorrhagic shock resulting in an ISS of 27. After polytrauma, the animals underwent resuscitation and surgical fracture fixation. Blood samples were withdrawn before and immediately after trauma, 24 and 72 h later. Different subsets of Treg, CD4+CD25+, CD4+CD25+FoxP3+, CD4+CD25+CD127- and CD4+CD25+CD127-FoxP3+ were characterized by flow cytometry. Results: Absolute cell counts of leukocytes were significantly increasing after trauma, and again decreasing in the follow-up in human and porcine samples. The proportion of human Treg in the peripheral blood of TP admitted to the ED was lower when compared to HV. Their numbers did not recover until 72 h after trauma. Comparable data were found for all subsets. The situation in the porcine trauma model was comparable with the clinical data. In porcine peripheral blood before trauma, we could identify Treg with the typical immunophenotype (CD4+CD25+CD127-), which were virtually absent immediately after trauma. Similar to the human situation, most of these cells expressed FoxP3, as assessed by intracellular FACS stain. Conclusion: Despite minor percental differences in the recovery of Treg populations after trauma, our findings show a comparable decrease of Treg early after polytrauma, and strengthen the immunological significance of the porcine polytrauma model. Furthermore, the Treg subpopulation CD4+CD25+CD127- was characterized in porcine samples.